Cerebral Venous Thrombosis with Migraine-Like Headache and the Trigeminovascular System - Fábio A. Nascimento; Marília Grando Sória; Vanessa Rizelio; Pedro A. Kowacs (Case Reports in Neurological Medicine)
Cerebral venous thrombosis- (CVT-) associated headache is considered a secondary headache, commonly presenting as intracranial hypertension headache in association with seizures and/or neurological signs. However, it can occasionally mimic migraine. We report a patient presenting with a migraine-like, CVT-related headache refractory to several medications but intravenous dihydroergotamine (DHE). The response to DHE, which is considered to be an antimigraine medication, in addition to the neurovascular nature of migraine, points out to a probable similarity between CVT-headache and migraine. Based on experimental studies, we discuss this similarity and hypothesize a trigeminovascular role in the genesis of CVT-associated headache.